(untitled) (Research, Society and Development, 2023)
The conservative treatment of urinary incontinence is performed by means of techniques aimed at strengthening the PA muscles. The choice of this theme enabled the discussion of physiotherapy and its role in the prevention and treatment of urinary incontinence in women’s health, promoting better body and perineal awareness, the main physiotherapeutic strategies used to prevent and treat this dysfunction. There are several risk factors and causes of UI, one of them being age, which is considered the main risk factor for urinary incontinence in women, which strongly affects the elderly, mostly women, usually from menopause. General Objective: To demonstrate the effectiveness of physical therapy intervention in the prevention and treatment of women’s health, discussing the profound impacts on the prevention and rehabilitation of various diseases that affect them. The research project is a bibliographic, descriptive and explanatory study, whose data collection will be carried out from the review of academic articles related to the topic in question. It is necessary to promote individuals’ access to this care and make them aware of the role of the professional in urinary tract diseases and promote better access to this care.